The Impact of Field Courses on Undergraduate Knowledge, Affect, Behavior, and Skills: A Scoping Review. (24th August 2022) - Shinbrot, Xoco A; Treibergs, Kira; Hernández, Lina M Arcila; Esparza, David; Ghezzi-Kopel, Kate; Goebel, Marc; Graham, Olivia J; Heim, Ashley B; Smith, Jansen A; Smith, Michelle K
Abstract: Field courses provide transformative learning experiences that support success and improve persistence for science, technology, engineering, and mathematics majors. But field courses have not increased proportionally with the number of students in the natural sciences. We conducted a scoping review to investigate the factors influencing undergraduate participation in and the outcomes from field courses in the United States. Our search yielded 61 articles, from which we classified the knowledge, affect, behavior, and skill-based outcomes resulting from field course participation. We found consistent reporting on course design but little reporting on demographics, which limits our understanding of who takes field courses. Cost was the most commonly reported barrier to student participation, and knowledge gains were the most commonly reported outcome. This scoping review underscores the need for more rigorous and evidence-based investigations of student outcomes in field courses. Understanding how field courses support or hinder student engagement is necessary to make them more accessible to all students.